Optimalisasi Pemasaran Produk Lokal Melalui Workshop Desain Grafis Dengan Canva pada Koperasi Wanita - Sanwani, Sanwani; Priyatna, Ade; Budi, Eko Setia; Zuraidah, Eva; Perwitasari, Ayu; Anggata, Aprio Riska; Agustina, Menik Anna; Krishandi, Septa Remond; Nursalim, Fredrika Irmanielyn (Journal of Social Responsibility Projects by Higher Education Forum, 2024)
Atsiri Women's Cooperative is a social organization as a forum and means of developing every member of society that grows and develops on the basis of social awareness and responsibility from and for the community in the region, especially engaged in medium and small businesses. While the membership of the Atssiti Citayem Cooperative, hereinafter referred to as the Cooperative Mothers, is every member of the community. Atsiri Women's Cooperative, Established on December 11, 2011, located at Jl. Jalan Sedap Malam Raya no 45 Rt 01 RW 12 Atsiri Permai Housing, Ragajaya Village, Bojonggede District. Bogor Regency. Postal Code 16920, Deed of Establishment of the "Atsiri Women's Cooperative" Cooperative Number: 252,- Date: April 03, 2012. Atsiri Women's Cooperative is engaged in the field of All Kinds of Business. The problem of limited understanding of social media management that has not been carried out in optimization in the UMKM management environment. The use of social media used is still manual for sales information. Therefore Therefore Nusa Mandiri University carries out Community Service in the form of training and utilization of Canva application technology in developing product sales. With this training, it can help Cooperative Mothers in managing and providing information data with training in implementing digital product sales. The output that will be achieved from the Socialization in the form of Community Service is publication in local print or electronic mass media.